2023
DOI: 10.15537/smj.2023.44.6.20230090
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric foreign body ingestion in Makkah, Saudi Arabia

Bayan O. Besharah,
Rehab F. Simsim,
Lina Y. Natto
et al.

Abstract: Objectives: To improve the local data and demographics of foreign body (FB) ingestion in the Makkah, Saudi Arabia and to provide basic statistics for future studies in the local community. Methods: We carried out a record-based retrospective epidemiological study of 153 pediatric patients with FB ingestion who presented to our center in Makkah, Saudi Arabia, between December 2014 and December 2019. Adult age, impacted FB at other sites, and chemical ingestion were exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(48 reference statements)
2
0
0
Order By: Relevance
“…This result agreed with a previous study done in 2017, which reported that age was one of the most influencing factors in FBI [13]. In our study, coin ingestion was the most common FBI type, representing 46.7% (n=111) of cases; 17.2% (n=40) of cases presented with battery ingestion, which was similar to studies done in Saudi Arabia in 2018 and 2023 [4,14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result agreed with a previous study done in 2017, which reported that age was one of the most influencing factors in FBI [13]. In our study, coin ingestion was the most common FBI type, representing 46.7% (n=111) of cases; 17.2% (n=40) of cases presented with battery ingestion, which was similar to studies done in Saudi Arabia in 2018 and 2023 [4,14].…”
Section: Discussionsupporting
confidence: 93%
“…The most commonly used procedure for FB removal was urgent endoscopy, accounting for 54.1% of all cases in our study, which was similar to another study [4]. In addition, in a study done in Makkah, 95.4% of FBI patients required urgent endoscopic removal of the FB [14]. Furthermore, in a study done in Kurdistan, out of 20 patients, 13 required endoscopic intervention [3].…”
Section: Discussionsupporting
confidence: 87%